2019
DOI: 10.21153/jtlge2019vol10no1art790
|View full text |Cite
|
Sign up to set email alerts
|

Does university prepare students for employment? Alignment between graduate attributes, accreditation requirements and industry employability criteria

Abstract: One of the primary goals of tertiary education is to prepare students for employment. There is debate as to whether university courses adequately provide students with 21st century workplace skills (Kaminski, Switzer, & Gloeckner, 2009; Kivunja, 2014). In a rapidly changing workforce, institutions must constantly adapt to maintain the practical utility of their courses. A thematic analysis was conducted to explore the degree of alignment between graduate attributes, accreditation requirements and industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…For instance, it was found that non-IT skills such as listening, interpersonal, and verbal communication were important for graduates' employability [45] and soft skills are important for accounting students' employability [8]. Employers prioritized graduates who possess skills such as problem solving and communication [36]. Communication, listening, and interpersonal skills were also recognized by managers as highly desired skills for business graduates in the banking industry [31] and graduates of management sciences [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was found that non-IT skills such as listening, interpersonal, and verbal communication were important for graduates' employability [45] and soft skills are important for accounting students' employability [8]. Employers prioritized graduates who possess skills such as problem solving and communication [36]. Communication, listening, and interpersonal skills were also recognized by managers as highly desired skills for business graduates in the banking industry [31] and graduates of management sciences [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, from the employers' perspectives, importance of soft skills was found to be important when recruiting business graduates [29]. Finally, studies on the employers' views of how well university graduates are prepared for the workplace as well as the alignment between university graduate attributes and accreditation requirements have been widely explored [20,31,34,35,36]. Therefore, the first hypothesis states that:…”
Section: Overview Of the Current Research On It And Non-it Skills For Business Graduatesmentioning
confidence: 99%
“…The current emphasis on skills development to enhance graduate employability by institutions is suggested by Clark et al (2011) and Jackson (2016) as being too narrow and insufficient to capture the full complexity of the task of preparing students to be purpose focussed in their working life. Many institutions have utilised the professional placement (internship or work placement) to provide students with the opportunity to develop their professional purpose toolkit as a key purpose to their graduate attributes (Rowe & Zegward, 2017;Oraison et al, 2019). This has enabled graduates the opportunity to mature their professional networks, understand their self and social awareness in relation to their chosen discipline, and provide insight into navigating their professional environment -opportunities that are difficult to replicate in a classroom (Bates et al, 2019;Moore & Morton, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Jollands et al (2015) found that maintaining partnerships with professional associations strengthened employability. Universities that boast high graduate employment rates focus on industry links and career development, and maintain ties with industry accrediting bodies, as the market increasingly favours industry-specific certifications, especially in the technical and financial arena (Oraison et al , 2019). Engaging Academics with industry experience to strengthen industry ties was evidenced in the findings of Rees (2019) as well as Santos (2020) and Belwal et al (2017).…”
Section: Institutional Driversmentioning
confidence: 99%